1995
DOI: 10.1017/s0021859600084823
|View full text |Cite
|
Sign up to set email alerts
|

The quantum yield of photosynthetic electron transport evaluated by chlorophyll fluorescence as an indicator of drought tolerance in durum wheat

Abstract: The chlorophyll fluorescence parameters AF/Fm ' and Fv'/Fm', related respectively to the quantum yield of photosynthetic electron transport and to the efficiency of excitation capture by the open centres of photosystem II, have been evaluated as possible indicators of drought tolerance in durum wheat. AF/Fm' and Fv'/Fm' measurements were carried out on excised leaves, both control and dehydrated, of 25 cultivars. AF/Fm' and Fv'/Fm' values were obtained at two times after the start of fluorescence measurement:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
4
23
0
1
Order By: Relevance
“…Other authors reported changes in ΔF/Fm′, which can be correlated to Y(II) (Klughammer and Schreiber, 2008). A 20% decrease in ΔF/Fm′ was previously found during the formation of the fluorescence induction curve, while no great differences were observed between control and dehydrated durum wheat leaves under steady state conditions (Flagella et al, 1995). In the present experiment, the cold-induced drop in Y(II) recovered to the level at growth temperature (21°C) under the effect of mild water stress.…”
Section: Discussionsupporting
confidence: 53%
“…Other authors reported changes in ΔF/Fm′, which can be correlated to Y(II) (Klughammer and Schreiber, 2008). A 20% decrease in ΔF/Fm′ was previously found during the formation of the fluorescence induction curve, while no great differences were observed between control and dehydrated durum wheat leaves under steady state conditions (Flagella et al, 1995). In the present experiment, the cold-induced drop in Y(II) recovered to the level at growth temperature (21°C) under the effect of mild water stress.…”
Section: Discussionsupporting
confidence: 53%
“…On the oth-er hand, the high concentration of chlorophyll b which enhances the utilization of carbon (IV) oxide to produce carbohydrate in T.grandis could be attributed to its ability to withstand extreme weather events than other tree species examined (Larcher 1995;Falk et al 1996;Carter and Knapp 2001;Richardson et al 2002;Khaleghi et al 2012;See Heschel et al 2014). This confirmed with the findings of Ekanayake et al (2004), Pervial and Sheriffs (2002), Flagella et al (1995) that chlorophyll concentration provides rapid and accurate techniques of detecting and quantifying plant tolerance to stress. This implies that trees with higher foliar chlorophyll content could have the ability to withstand adverse weather events as would increase their adaptive capacity.…”
Section: Chlorophyll Concentrationsupporting
confidence: 90%
“…When chlorophyll absorbs light energy the molecules enters into a higher energy state in which it easily gives up an electron to the first available electron-accepting molecules nearby (Flagella et al 1995). Leaf chlorophyll probe is a powerful and sensitive intrinsic measurement of the photosynthetic process (Oquist and Wass 1988), which can be used to detect the influence of various environmental stress factors (Oyetunji et al 2007;Richardson et al 2002;Flagella et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the maximum quantum yield of PSII photochemistry (F v /F m ) implies a decrease in the capture and conversion rate of excitation energy by PS II reaction centres and so, a reduction in PS II photochemical efficiency (Flagella et al, 1995). These results indicate the disorganisation of PS II reaction centres under water stress conditions (Giardi et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…This disorder appeared to be highly pronounced in TN88-63 (the moderately sensitive cowpea) than in B21 (the resistant cowpea). Otherwise, the increase in ABS/RC would be a survival strategy consisting in over-activity of unaltered reaction centres to maintain some energy absorption rate without compensating the lost of maximum quantum yield of photosystem II (Flagella et al, 1995). Sharma et al (2005) found that the overproduction of antioxidative enzymes (SOD and peroxidase) was accompanied by the reduction of the net photosynthetic rate, stomatal conductance and transpiration rate in wheat genotypes.…”
Section: Discussionmentioning
confidence: 99%